Influence of flexible goals on motivational sphere of university teachers - O. . Nazarova (Высшее образование в России)
The article analyzes the approaches to the development of motivation of university teachers and students in their joint activities. Describes the mechanisms for the formation of flexible goals and their impact on the motivation sphere of university teachers. The paper analyzes the principles of designing coherent and effective system of remuneration of employees of educational institutions based on relative targets.